MODEL PENGELOLAAN EKOWISATA BERKELANJUTAN BERBASIS MASYARAKAT SUATU ANALISIS BIBLIOMETRIK DAN TINJAUAN LITERATUR - Mohamad, Nurdin; Lihawa, Fityane; Hasim; Wahyuni K. Baderan, Dewi; Mahmud, Marike; Jaya Lahay, Rakhmat (Universitas Cokroaminoto Palopo, 2024)
Ecotourism is a concept driven by tourist demand, while sustainable tourism includes measures to preserve the environment from the supply side, meaning by tourism service providers. Ecotourism management cannot be separated from the involvement of the community around the ecotourism area, because the community is the main key to the success of a holistically sustainable ecotourism area. This article aims to find out the extent to which similar research has been carried out based on searches on sciencedirect by looking for relationships based on keywords. The method used in this literature review is bibliometrics, namely a descriptive quantitative method, which was obtained through a web search with the site address https:www.sciencedirect.com.Where the literature data comes from Scopus with the publication type Article and uses a range of publication years between 2018 and 2024. The analysis used in this literature review is using Co-occurrence with the keyword Co-occurrence limit 12 and obtained 5 clusters. using coral reef ecotourism analysis, where there are 18 keywords divided into 5 clusters, each group has characteristics represented by one color. These keywords are spread across 401 articles over a period of 7 years, namely from 2018 to 2024. The conclusion is that the closeness between keywords can indicate the number of topics studied and researched by researchers, namely coralreef ecotourism and coralreef biodiversity, coralreef sustainable tourism and Corarseef Conservation.